2016
DOI: 10.1124/dmd.115.068577
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Developmental Trajectory of Human Hepatic Membrane Transporter Proteins in the First Three Months of Life

Abstract: Human hepatic membrane-embedded transporter proteins are involved in trafficking endogenous and exogenous substrates. Even though impact of transporters on pharmacokinetics is recognized, little is known on maturation of transporter protein expression levels, especially during early life. We aimed to study the protein expression of 10 transporters in liver tissue from fetuses, infants, and adults. Transporter protein expression levels [ATP-binding cassette transporter (ABC)B1, ABCG2, ABCC2, ABCC3, bile salt ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
7
25
1
Order By: Relevance
“…P‐gp expression levels in the liver only reached 50% of adult expression levels at 2.9 years of age, whereas our results suggested that full adult levels were achieved in the kidneys by that age. For BCRP, our results for mRNA expression in the kidneys were consistent with that in the liver, which showed a decline from newborns to adults . As more transporter ontogenetic data in different organs become available, more reliable prediction in transporter‐mediated substrate disposition on the whole‐body level during development will be achieved.…”
Section: Discussionsupporting
confidence: 75%
“…P‐gp expression levels in the liver only reached 50% of adult expression levels at 2.9 years of age, whereas our results suggested that full adult levels were achieved in the kidneys by that age. For BCRP, our results for mRNA expression in the kidneys were consistent with that in the liver, which showed a decline from newborns to adults . As more transporter ontogenetic data in different organs become available, more reliable prediction in transporter‐mediated substrate disposition on the whole‐body level during development will be achieved.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, most of these human transporter mRNA expression data are limited to fetal livers . Proteomics quantification of 10 drug transporters (excluding OCT1 and OATP1B3) in human livers has recently been reported . However, because this study was primarily based on the limited number of fetal and infant samples, the developmental patterns are not conclusive.…”
mentioning
confidence: 97%
“…Findings of studies on the developmental pattern of the ABCC3 transporter during childhood are inconsistent. Based on the proteomic study that did illustrate a "low to high" developmental pattern, adult protein expression values are reached within the first 5 postnatal weeks (40 ). Therefore, it would be worthwhile to assess if the reported effect of the Ϫ211CϾT variant on morphine PK could also be found in the neonatal population.…”
Section: Abcc3mentioning
confidence: 99%